We Must Be Brave - Liardet, Frances (London : 4th Estate, 2019)
In the disorderly evacuation of Southampton, England, newly married Ellen Parr finds a small child asleep on the backseat of an empty bus. No one knows who little Pamela is. Ellen professed not to want children with her older husband, and when she takes Pamela into her home and rapidly into her heart, she discovers that this is true: Ellen doesn't want children. She wants only Pamela. Three golden years pass as the Second World War rages on. Then one day Pamela is taken away, screaming. Ellen is no stranger to sorrow, but when she returns to the quiet village life she's long lived, she finds herself asking: In a world changed by war, is it fair to wish for an unchanged heart? A story of courage and kindness, hardship and friendship, this novel explores the fierce love we feel for our children and the astonishing power of that love to endure.
Keywords: World War, 1939-1945 -- Evacuation of civilians -- Fiction -- England -- Southampton; Abandoned children -- Care -- Fiction; Adoptive parents -- Fiction; Domestic fiction